1996
DOI: 10.1073/pnas.93.4.1636
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of the endogenous neuroexcitotoxin quinolinate in human peripheral blood monocytes/macrophages and the effect of human T-cell lymphotropic virus type I infection.

Abstract: Immunocytochemical localization of the endogenous neuroexcitotoxin quinolinate in human peripheral blood monocytes/macrophages and the effect of human T-cell lymphotropic virus type I infection Contributed by D. Carleton Gajdusek October 19, 1995 ABSTRACT Quinolinate (Quin), a metabolite in the kynurenine pathway of tryptophan degradation and a neurotoxin that appears to act through the N-methyl-D-aspartate receptor system, was localized in cultured human peripheral blood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…8). In support of this model, we and colleagues have shown that macrophages and microglia can metabolize KYN to QUIN (Venkateshan et al . 1996; Heyes et al .…”
Section: Discussionmentioning
confidence: 53%
“…8). In support of this model, we and colleagues have shown that macrophages and microglia can metabolize KYN to QUIN (Venkateshan et al . 1996; Heyes et al .…”
Section: Discussionmentioning
confidence: 53%
“…Based upon previous immunohistochemical studies that have demonstrated that strong staining for quinolinate is limited to cells of the immune system, we have postulated that quinolinate serves an immune-system-specific function (Moffett et al 1994a(Moffett et al ,b, 1997Espey et al 1995Espey et al , 1996Venkateshan et al 1996;Namboodiri et al 1996). The present study has been designed to assess the effect of increased extracellular tryptophan and kynurenine on quinolinate staining in several organs known to contain varying amounts of quinolinate (Saito et al 1993b).…”
Section: Discussionmentioning
confidence: 92%
“… 50 , 51 , 52 In the liver, it is well documented that hepatocytes produce quinolinate transiently in the course of NAD + synthesis, 49 but quinolinate does not accumulate in the liver under normal conditions 53 . Monocytes have been found to be robust producers of quinolinate when stimulated with IFN‐γ and other immune stimulants 54 , 55 , 56 . In fact, the spleen has one of the highest levels of quinolinate in any tissue or organ 42…”
Section: Quinolinate and The Immune Systemmentioning
confidence: 99%